2018
DOI: 10.1111/myc.12768
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal treatment in haematological and oncological patients: Need for quality assessment in routine care

Abstract: Invasive fungal infections in haematological and oncological patients have a major impact on morbidity, mortality and treatment costs. Therefore, rational use of antifungal agents is important for optimal patient care and resource use. The study's objective was to analyse antifungal usage in a German tertiary teaching hospital, department of haematology and oncology, to evaluate quality of antifungal treatment and to assess the need for an antifungal stewardship programme. This retrospective observational stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 33 publications
0
26
0
2
Order By: Relevance
“…For example, studies have shown that up to 50% of antifungals are inadequately dosed and that certain antifungals require multiple dose adjustments to achieve therapeutic levels. 5,28,30,31 Our study revealed variability in the target therapeutic levels reported across institutions, which suggests a lack of consensus in current practices and an important opportunity for standardization. Many of the survey respondents reported a lack of confidence in making antifungal recommendations.…”
Section: Discussionmentioning
confidence: 88%
“…For example, studies have shown that up to 50% of antifungals are inadequately dosed and that certain antifungals require multiple dose adjustments to achieve therapeutic levels. 5,28,30,31 Our study revealed variability in the target therapeutic levels reported across institutions, which suggests a lack of consensus in current practices and an important opportunity for standardization. Many of the survey respondents reported a lack of confidence in making antifungal recommendations.…”
Section: Discussionmentioning
confidence: 88%
“…Table 3 summarizes key elements of the included studies. [12][13][14][15][16][17][18][19] Five studies assessed adherence to antifungal guidelines in the inpatient setting, and 5 studies assessed the impact of an inpatient antifungal stewardship program on the appropriateness of fungal therapy. No studies of antifungal adherence in the outpatient setting were found.…”
Section: Data Synthesismentioning
confidence: 99%
“…Forty patients (30%) died during their hospitalization due to concomitant disease (31 cases), underlying conditions (6 cases), and fungal infection (3 cases). 12 The study by Lachenmayr et al 13 was a retrospective review of 104 patients receiving antifungal treatment and prophylaxis in the Hematology and Oncology departments of a German teaching hospital (Table 3). This included 61 patients (58.7%) with AML, 18 (17.3%) with lymphoma, 5 (4.8%) with ALL, 5 (4.8%) with multiple myeloma, and 3 (2.9%) with myelodysplastic syndrome.…”
Section: Assessing Adherence To Antifungal Guidelinesmentioning
confidence: 99%
“…Prophylaxis with the antifungal agent posaconazole reduced the rate of IFI and mortality in AML patients with neutropenia after induction chemotherapy . Although it is therefore strongly recommended by international guidelines, the use of systemic antifungal agents differs from guidelines for various reasons (eg, intolerance, drug interactions) in a substantial number of cases in clinical routine . In comparison with other established broad‐spectrum antimycotics, posaconazole is effective against mould as well as yeast infections, has a better safety profile and shows advantages concerning drug–drug interactions …”
Section: Introductionmentioning
confidence: 99%
“…3,4 Although it is therefore strongly recommended by international guidelines, 5,6 the use of systemic antifungal agents differs from guidelines for various reasons (eg, intolerance, drug interactions) in a substantial number of cases in clinical routine. 7 In comparison with other established broad-spectrum antimycotics, posaconazole is effective against mould as well as yeast infections, has a better safety profile and shows advantages concerning drug-drug interactions. 8 The oral suspension was approved for antimycotic prophylaxis in patients with AML during induction chemotherapy and stem cell transplant recipients with graft-vs-host disease (GVHD) grade II or higher in 2007.…”
Section: Introductionmentioning
confidence: 99%